Madrasah Education System And Terrorism: Reality And Misconception - Mohd Izzat Amsyar Mohd Arif; Nur Hartini Abdul Rahman; Hisham Hanapi (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
Since the terrorist attacks on September 11, 2001, the Islamic schools known as madrasah havebeen of increasing interest to analysts and to officials involved in formulating U.S. foreign policytoward the Middle East, Central, and Southeast Asia. Madrasah drew added attention when itbecame known that several Taliban leaders and Al-Qaeda members had developed radicalpolitical views at madrasah in Pakistan, some of which allegedly were built and partially financedthrough Saudi Arabian sources. These revelations have led to accusations that madrasah promoteIslamic extremism and militancy, and are a recruiting ground for terrorism. Others maintain thatmost of these religious schools have been blamed unfairly for fostering anti-U.S. sentiments andargue that madrasah play an important role in countries where millions of Muslims live in povertyand the educational infrastructure is in decay. This paper aims to study a misconception of therole and functions of Islamic traditional religious schools which have been linked with theactivities of terrorism. The study will be specifically focus on practice of the traditional Islamicschool, which is locally called as ‘madrasah system’.